EFFECTIVENESS OF Exoecaria agallocha SUBSTANCE POWDER AS MOLLUSCICIDE ON SNAIL MUD PEST (Ceritidea sp.) - Puspitasari, Indah; Suseno, Dewi Nurmalita; Jayanti, Shara (Chanos Chanos, 2021)
The use of chemical-based molluscicides at the preparation stage of aquaculture activities in ponds can cause residues and death of biota other than mollusc pests and ultimately cause environmental damage. Because of this, natural ingredients are needed. A study on the effectiveness of Excoecaria agallocha gum powder as a molluscicide against Trisipan Cerithidea sp. has been carried out during September - November 2020 in Pulokerto Village, Kraton District, Pasuruan Regency, East Java. The sap from the E. agallocha tree was tapped and made into powder, then tested on 10 trisipans per aquarium, with concentrations of 0, 200, 400, 800, 1600 ppm and control with 3 repetitions. Mortality observations were carried out for 24 hours. The results of the characteristic analysis showed that the E. agallocha latex powder had an ash content of 7.73%, water content of 3.08%, pH 10. The content of bioactive compounds from E. agallocha gum powder using 70% methanol solution included saponins and triterpenoids. The concentration of latex powder has a high influence on the mortality of Cerithidea sp. (Linear regression, R2 = 0.8762) and had a significantly positive relationship (Pearson correlation test, r = 0.936, P = 0.019). Significant differences were found in the mortality of Cerithidea sp. with treatments of 800 and 1600 ppm which were significantly different with concentrations of 200 and 400 ppm (One-way Anova, F = 29.50, P <0.05, df = 3, Tukey test). Toxicity test showed 24-hour LC50 of E. agallocha latex powder against Trisipan Cerithidea sp. is 688.89 ppm and can be categorized as toxic.